Molecular Modeling and in Silico Characterization of a Pathogenesis-Related Protein-10 (PR10) and its Coding Genes in some Oryza Species (Baghdad Science Journal, 2019)
Rice is a major staple food for more than two thirds of the world population. Pathogenesis-related proteins-10 (PR10) have a range of 154 to 163 amino acid with molecular weight ~ 17 kDa. They are acidic and generally intracellular and cytosolic proteins accumulate in plants in response to biotic and abiotic stresses. In the present study, a PR10 gene and its corresponding protein were characterized in O. sativa, O. barthii, O. glaberrima, O. glumipatula, O. meridionalis, O. nivara, O. rufipogon and O. punctata. The results revealed a narrow range of variation at both DNA and protein levels in all examined species except O. glumipatula. The latter showed a relatively obvious structural variation at protein level. Such variation may be beneficial against different types of stress that requires further elucidation to exploit in rice breeding programs.